Moving In-Between: The Interpreter as Ethnographer and the Interpreting-Researcher as Anthropologist - Bahadır, Şebnem (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractMy starting point in this article is the community interpreter who works in social, medical and legal settings, under specific conditions, confronting very delicate ethical problems. In search of a theoretical framework that accounts for the social roles and cultural identities of the community interpreter I began to re-read the German anthropologist and conference interpreter Heinz Göhring. His articles can be positioned between German Studies (‘Deutsch als Fremdsprache‘), intercultural communication studies (including cultural anthropology) and translation studies. I start out with his view of an ideal translator/ interpreter as cultural expert acting like a “mini-ethnographer” and try to go beyond Göhring by connecting his ideas to the concept of the critical ethnographer as model for a professional community interpreter. In this theoretical discussion I want to show how a synthesis of the framework proposed by Göhring and recent anthropological theories can be used for a new professional profile of the interpreter, not only in community settings but in general. Besides aspects concerning translation/ interpreting politics, I wish to foreground that a re-thinking of interpreter roles would/ should also affect translation/ interpreting pedagogy and research.